2020
DOI: 10.4103/jrms.jrms_918_19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal triclosan exposure on gestational age and anthropometric measures at birth: A systematic review and meta-analysis

Abstract: Background: Exposure to endocrine disrupting chemicals such as triclosan (TCS) leads to disrupting the endocrine system and consequently effect on the birth outcomes. The findings of studies in this field are controversial. Materials and Methods: This systematic review and meta analysis was conducted based on the identified published papers in Scopus, Web of Science, and PubMed up to November 2019. All steps, including searching, screening, data extracting, and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…To explore the reasons for the existence of heterogeneity, we performed subgroup analysis and sensitivity analysis for the results, while Zhong et al ( 37 ) did not. However, the result of our study differs from the article published in June 2020 ( 38 ), which showed that exposure to TCS during pregnancy will increase the birth weight of newborns. However, the CI for the results of the study on birth weight crossed zero in the forest plot, indicating that their results were not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…To explore the reasons for the existence of heterogeneity, we performed subgroup analysis and sensitivity analysis for the results, while Zhong et al ( 37 ) did not. However, the result of our study differs from the article published in June 2020 ( 38 ), which showed that exposure to TCS during pregnancy will increase the birth weight of newborns. However, the CI for the results of the study on birth weight crossed zero in the forest plot, indicating that their results were not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%